Nanofibrous Scaffolds for Diabetic Wound Healing - Anna Yusuf Aliyu; Oluwatoyin A. Adeleke (MDPI AG, 2023)
Chronic wounds are one of the secondary health complications that develop in individuals who have poorly managed diabetes mellitus. This is often associated with delays in the wound healing process, resulting from long-term uncontrolled blood glucose levels. As such, an appropriate therapeutic approach would be maintaining blood glucose concentration within normal ranges, but this can be quite challenging to achieve. Consequently, diabetic ulcers usually require special medical care to prevent complications such as sepsis, amputation, and deformities, which often develop in these patients. Although several conventional wound dressings, such as hydrogels, gauze, films, and foams, are employed in the treatment of such chronic wounds, nanofibrous scaffolds have gained the attention of researchers because of their flexibility, ability to load a variety of bioactive compounds as single entities or combinations, and large surface area to volume ratio, which provides a biomimetic environment for cell proliferation relative to conventional dressings. Here, we present the current trends on the versatility of nanofibrous scaffolds as novel platforms for the incorporation of bioactive agents suitable for the enhancement of diabetic wound healing.